Perjanjian Kerja Waktu Tertentu (PKWT) Berdasarkan UU No 6/2023 Tentang Cipta Kerja Dan Hukum Islam - Deni Iskandar; Nurul Amalia; Muhammad Misbakul Munir (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This research explores the Specific Time Work Agreement (PKWT) between workers and PT. Astra Autoparts. Using qualitative methods and a normative juridical approach, this research not only refers to regulations and related literature, but also involves observations and interviews with HRD and contract workers at the company. From an Islamic legal perspective, research emphasizes that PKWT must fulfill the principles of justice, equality and protection of workers' rights. The concept of